Membangun Konstruksi Sosial Anak Melalui Pendidikan Keluarga Perspektif Al-Qur’an: Analisis Pemikiran Muhammad Hamka dalam Tafsir Al-Azhar - Adawiyah, Robiatul; Rahardja, Muhammad Nurfaizi Arya; Hasibuan, Ulfah Salwa (UIR Press, 2024)
This research aims to reveal and know the role of family education in building social construction offered by Hamka in Tafsir al-Azhar as an effort to provide solutions to the community regarding the attitude that families need to take in implementing education. This research is qualitative by using library research to obtain research data and is descriptive-applicative. The main source in this research is Tafsir al-Azhar by Hamka and the secondary sources in this research are articles, scientific works, and documents relevant to this research. The results of this study are, first, according to Hamka to justify a society must justify its main joints, namely a person's soul, second, according to Hamka, fathers and mothers have an important role in the family to shape the soul of a child and parents must ensure that they provide good education to children so that children will be able to live social life in society well.